Optimasi Nanoemulsi A/M/A Ekstrak Etanol Daun Binahong dan Konjugat AG-Kitosan Menggunakan Desain Box-Behnken - Malinda Prihantini; Irda Fidrianny; Tri Suciati (Fakultas Farmasi Universitas Pancasila, 2019)
Skin premature aging which is characterized by fine wrinkles can be overcome by stimulating collagen production and inhibiting its degradation, and also reducing corneocyte buildup. Madeira vein has been shown to induce collagen production and inhibit its degradation, while glycolic acid increase desquamation. The aim of this research was to optimize W/O/W multiple nanoemulsion formula of Madeira vein-leaves extract in W1 phase and glycolic acid in W2 phase. Glycolic acid was added after conjugated with chitosan to reduce its stinging effect on skin. The W/O/W multiple nanoemulsion was prepared through two emulsification steps: W1/O primary emulsion using high speed homogenizer, and the secondary emulsion using magnetic stirrer. W1/O was optimized including the selection of co surfactant and extract concentration, followed by secondary emulsion optimization using response surface methodology consisted of 2-level factorial and Box-Behnken design. The W1/O consisted of extract, polysorbate 80 as surfactant, PEG 400 as co surfactant and isopropyl myristate as oil phase. The 2-level factorial gave the three significant factors: W1/O sonication time, W1/O concentration, and secondary emulsification stirring time. Box-Behnken optimization for globule size below 400 nm was obtained by 6-10 minutes W1/O sonication time, 12-16% W1/O concentration, and 32-42 minutes stirring time of secondary emulsification.